Comparative Analysis of Bio-Intermediates and Waste-Derived Fuels in Experimental Gas Turbine - Rosec, Žiga; Dias, Véronique; Contino, Francesco; Katrašnik, Tomaž; Seljak, Tine (Frontiers in Mechanical Engineering, 2020)
The paper presents a first comparative analysis of emission formation phenomena of three different bioliquids, derived from low cost waste streams while utilizing the same, gas turbine based experimental setup. A consistent and unbiased comparison is ensured by the application of the same experimental test rig featuring only those minor fuel based adaptions, which are required to ensure most favourable operation of each of the analysed fuels. This provides the direct comparative data between combustion performance of liquefied wood, obtained through solvolysis process, glycerol and waste liquor from nanocellulose production that were previously tested in various combustion systems, hence making direct evaluation of fuel’s suitability difficult. The study focuses on analysis of all key thermodynamic parameters, significant emission species covering CO, NOx, HC particulate matter and soot as well as identification of underlying phenomena for observed emission trends. These indicate that for NOx emissions a good correlation exists to stoichiometric ratio of the fuels, where low stoichiometric ratio results in lower NOx emissions, provided oxygen content is the main diluent and fuel bound nitrogen is low. As all tested fuels feature oxygen content above 43%, this enables a large improvement in NOx – CO trade off, as CO emissions are reducing with higher peak combustion temperatures while minimally increasing NOx emissions. Similar observations are made for particulate matter – NOx trade off, however the ash content significantly impacts the particulate matter emission, hence reducing the potential for clean combustion of waste liquor. In the case of glycerol with no ash content, soot emissions are minimal and for an order of magnitude lower than for benchmark diesel fuel, as there are numerous phenomena effectively reducing their formation and increase their oxidation. The presented research confirms that utilization of bio-intermediates and waste-derived fuels in appropriate combustion setups can beside low CO2 footprint, feature also very low emissions of other pollutant species, providing that fuels feature high oxygen content, low ash content and low nitrogen content. With such approach it is possible to achieve clean combustion that is fully in line with circular economy guidelines.